Housefly (Musca domestica) larvae powder, preventing oxidative stress injury via regulation of UCP4 and CyclinD1 and modulation of JNK and P38 signaling in APP/PS1 mice. Issue 1 (12th December 2018) - He, Yinru; Yang, Xia; Jiao, Mengya; Anoopkumar-Dukie, Shailendra; Zeng, Yu; Mei, Hanfang
Abstract : Housefly ( Musca domestica ) Larvae powder (HL) is rich in antioxidants. Abstract : Housefly ( Musca domestica ) Larvae powder (HL) is rich in antioxidants. As oxidative stress is considered as one of the main pathogenesis in Alzheimer's Disease (AD), this study was designed to explore the protective effects of HL as an antioxidant on APP/PS1 mice. 2-Month-old APP/PS1 mice were divided into a model control (MC) group, a Donepezil group and a HL group, and C57BL/6 mice were used as the normal control (NC) group. After 180 days of treatment, the memory ability was measured by Morris Water Maze (MWM). The presence of Aβ and the expression of Uncoupling Protein 4 (UCP4) and CyclinD1 were detected by immunohistochemistry. The expressions of Superoxide Dismutase 1 (SOD1), Catalase (CAT) and Mitogen-activated Protein Kinase (MAPK) signal pathways were measured by western blotting. Compared with untreated APP/PS1 mice, the memory abilities of the HL-treated mice were significantly improved. Furthermore, the HL treatment not only down-regulated the deposition of Aβ and the expression of CylinD1, but also increased both the mRNA and protein levels of SOD, CAT, and UCP4, and enhanced the phosphorylation of JNK and P38 MAPK activation. In conclusion, these results suggest that HL may have a protective effect against memory impairment and prevent oxidative stress-induced injury via the regulation of UCP4 and CyclinD1 and the modulation of JNK and P38 MAPK signaling in AD.